Zinc fractionation in cow, goat, sheep and soybean milk samples using gel-electrophoresis and determination by electrothermal atomic absorption spectrometry (ETAAS) - Bossu, Carla Maíra; Giglioti, Rodrigo; Oliveira, Marcia Cristina de Sena; de Oliveira, Pedro Vitoriano; Nogueira, Ana Rita de Araujo (Eclética Química, 2021)
A screening method for zinc levels in different milk samples (raw cow, raw sheep, UHT cow, UHT goat and soybean milk base) was performed to establish the Zn levels’ differences in protein samples. The samples were digested in a cavity microwave oven and the total Zn levels in the extracts were determined by flame absorption atomic spectrometry (FAAS). The protein separation was performed by urea polyacrylamide gel electrophoresis (UREA-PAGE). Protein bands were digested in the cavity microwave oven and Zn-protein analysis was further conducted by electrothermal atomic absorption spectrometry (ETAAS). The results showed that Zn is mainly bound to 32 kDa (β-casein) protein (17.0 ± 2.0%) in UHT cow and 24 kDa (α-casein) protein (9.0 ± 0.6%) in raw sheep milk. This method provided quantitative information regarding Zn species present in the protein fractions of the milk samples. The accuracy was evaluated using certified reference material (whole milk powder, NIST 8435) with statistically equivalent concentrations (Student’s t-test) for total Zn and by addition and recovery experiments applied to measure Zn-protein. The recovered values were in the 92-110% range.